2020
DOI: 10.1038/s41598-020-77344-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of glaucoma in the Russian Ural Eye and Medical Study

Abstract: To assess the prevalence and associated factors of glaucoma in a Russian population. The population-based Ural Eye and Medical Study included 5899 (mean age 59.0 ± 10.7 years; range 40–94 years). Glaucomatous optic neuropathy was diagnosed using International Society of Geographical and Epidemiological Ophthalmology (ISGEO) criteria. Among 5545 participants with assessable optic disc photographs, 246 individuals [4.4%; 95% confidence interval (CI) 3.9, 5.0] had glaucoma, with open-angle glaucoma (OAG) in 177 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Five studies reported multiple alcohol exposure levels, and a single pooled effect estimate across all levels was calculated for use in meta-analysis. 26 , 28 30 , 67 Overall, 10 studies reported no association between any alcohol use and OAG, 16 , 23 31 with only one large cohort study of Black women reporting a harmful association. 67 Although there was a suggestion of a dose–response effect in those studies reporting ordinal alcohol exposure levels, 26 , 28 , 30 , 67 no study-specific test for trend reached statistical significance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies reported multiple alcohol exposure levels, and a single pooled effect estimate across all levels was calculated for use in meta-analysis. 26 , 28 30 , 67 Overall, 10 studies reported no association between any alcohol use and OAG, 16 , 23 31 with only one large cohort study of Black women reporting a harmful association. 67 Although there was a suggestion of a dose–response effect in those studies reporting ordinal alcohol exposure levels, 26 , 28 , 30 , 67 no study-specific test for trend reached statistical significance.…”
Section: Resultsmentioning
confidence: 99%
“…One further cross-sectional study 50 was included in the IOP analysis but excluded from the OAG analysis, because a second study from the same population 29 provided prospective data with greater adjustment for confounding variables. A further 5 articles 23 , 24 , 27 , 31 , 51 were identified from a reference list search of all included studies and previous reviews for a total of 34 articles included in the systematic review. This included 8 studies with IOP as the outcome, 24 with OAG as the outcome, and 2 with both IOP and OAG as outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No patients with OAG revealed an AL longer than 26 mm in our study population, but the results of that research may imply that IOP elevation may easily occur in patients with OAG and short AL. Since OAG tends to develop in patients with longer AL according to a population-based study [23], individuals with OAG and short AL might have certain factors that predispose them to IOP elevation and glaucoma progression. Further study is needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%